(3GdCMcGe aj JMhjd GdfLhes - (3Sgd Hf HTQ Hf MHjH Hf gGfj, CHh YKeGf GdESQGFjdj,J (B235 (3g` s
(3ChdgG (B:s
(3cJGH UfYI Ydi JMGhjd Sfi GdYGde , heG jMOK ai GdYGde , heG jUjH cd Ebdje heOfjI ef GdCef hGdNha hGdMQhH hGdeVGQ , heG jUjH edhcg HGdEbdje s
(3BNQgG (B:s
(3aEPG cGf GdcSha ai ehVhY ef Gdadc aGfXQ ef Ci GdLhGfH Jdc GdOQLI , aai Pdc GdLGfH jchf GdNjQ hGdTQ ajeG jOd Ydjg GdcSha, hGdMeO ddg Je cJGH GdJMGhjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG HYV GdLOGhds
(3HBNQgG Jedc deYde ai YOf SfI (B1312(3g`s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B283s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B252 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B396 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs